Empowering Educators as Designers: The Impact of EdTech on Language Teachers’ Instructional Decision-Making - Dr.K. Jaya (ILN Journal: Indian Literary Narratives, 2025)
The integration of Educational Technology (EdTech) has significantly reshaped language teaching, offering educators new tools for instructional design. This study explores the role of EdTech in enhancing language teachers’ instructional decision-making and examines how they navigate technological affordances to design effective learning experiences. Using a mixed-methods approach, the research investigates teachers’ perceptions of EdTech, the extent to which they exercise agency in technology integration, and the challenges they encounter in balancing pedagogical goals with digital tools.Data collection includes surveys and semi-structured interviews with language teachers across various educational settings. The findings highlight that EdTech enhances creativity and personalization in lesson planning but also brings challenges like digital literacy gaps, institutional policies, and platform limitations. Teachers who engage in professional development and reflective practice demonstrate greater autonomy and confidence in integrating technology effectively. The study underscores the need for targeted training programs that equip language teachers with the necessary skills to make informed instructional decisions in digital learning environments. These findings contribute to the broader discourse on teacher agency, digital pedagogy, and technology-enhanced language education, emphasizing the evolving role of teachers as designers of learning experiences.